1994
DOI: 10.1088/0022-3727/27/12/026
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of thermally stimulated currents

Abstract: While thermally stimulated depolarization currents, sometimes in conjunction with the thermal slicing technique, are often used to determine the activation energies and relaxation times of the processes occurring in a material, little attention has been paid to the question of whether the results do represent the true properties of the system. In this paper, a theoretical analysis and the results of calculations are presented for systems whose isothermal behaviour can be described in terms of a distribution of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

1997
1997
2010
2010

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 13 publications
1
16
0
Order By: Relevance
“…In addition, such materials often obey the time/temperature superposition principle, and so the response of the system can be analysed in terms of a reduced time [51][52][53]. It was reported that the commonly observed power-law behaviour in frequency imposes a quite general type of response on experiments performed in nonisothermal conditions [53].…”
Section: Fundamentals and Advantages Of Tsdc Technique And Comparisonmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, such materials often obey the time/temperature superposition principle, and so the response of the system can be analysed in terms of a reduced time [51][52][53]. It was reported that the commonly observed power-law behaviour in frequency imposes a quite general type of response on experiments performed in nonisothermal conditions [53].…”
Section: Fundamentals and Advantages Of Tsdc Technique And Comparisonmentioning
confidence: 99%
“…It was reported that the commonly observed power-law behaviour in frequency imposes a quite general type of response on experiments performed in nonisothermal conditions [53]. In a measurement of TSDC the reduced time ξ scales linearly with the inverse of heating rate b [51][52][53] dn…”
Section: Fundamentals and Advantages Of Tsdc Technique And Comparisonmentioning
confidence: 99%
“…TSDC has high sensitivity and the ability to selectively probe the relaxation kinetics during heating in a very restricted range of temperatures, by the TS method, 32 in which the polarization is applied in a narrow window ⌬T Ϸ 5 K. Note that in TS the Bucci method 33 is applied for the calculation of the relaxation time, so that each peak is considered, to a first approximation, as correspondent to a Debye process, characterized by a single value of the relaxation time parameters. The TS method in polymers therefore consists on fitting the depolarization peaks to Arrhenius-or Eyring-type equation and provides a value of E act associated to the chosen polarization temperature T p .…”
Section: ͑13͒mentioning
confidence: 99%
“…2 In spite of the advantages of TSDC for characterizing the relaxation processes of polymers, the interpretation of the TSDC spectra is still controversial. 9,10 The TSDC peaks are commonly interpreted on the basis of a distribution of relaxation times with an Arrhenius temperature dependence. 3,11,13 In order to "isolate" each of the relaxation components, several techniques involving partial polarization of the sample are used.…”
Section: Introductionmentioning
confidence: 99%